Japan's Household Savings Rate : An Application of the Life-Cycle Hypothesis. (IMF Working Papers; Working Paper ;, 1987)
This paper develops and tests a model of Japan's household savings rate, based on the life-cycle hypothesis that the primary motive for savings is provision for retirement. The paper shows that Japan's high household savings rate in recent decades reflects the positive influence of rapid economic growth, leading to a prolonged retirement period through the wealth and life-expectancy effects of an income change, which has initially outweighed the negative combined influence of improvements in public pension benefits and the aging of the population. It projects that the savings rate will decline substantially in coming decades as the negative influence accelerates.